StockTwits classified sentiment and stock returns - Divernois, Marc-Aurèle,Filipović, Damir (Swiss Finance Institute, 2021)
We classify the sentiment of a large sample of StockTwits messages as bullish,bearish or neutral, and create a stock-aggregate daily sentiment polarity measure.Polarity is positively associated with contemporaneous stock returns. On average,polarity is not able to predict next-day stock returns. But when we focus on specificevents, defined as sudden peaks of message volume, polarity has predictive power onabnormal returns. Polarity-sorted portfolios illustrate the economic relevance of our sentiment measure
10.2139/ssrn.3657034
Keywords: Graue Literatur; investor sentiment; event study; social media; micro-blogs; natural language processing